Matrix metalloproteinase-10 promotes kidney fibrosis by transactivating β-catenin signaling - Xiaoli Sun; Qian Ren; Xi Liu; Huishi Tan; Zhanji Zhan; Enqing Lin; Yinyi Long; Xue Hong; Lili Zhou; Youhua Liu (Cell Death Discovery)
Abstract Kidney fibrosis is characterized by excessive accumulation of extracellular matrix (ECM) and serves as a hallmark of chronic kidney disease (CKD). The turnover of ECM is controlled by a family of matrix metalloproteinases (MMPs), endopeptidases that play a crucial role in ECM remodeling and other cellular processes. In this study, we demonstrate that MMP-10 was upregulated in a variety of animal models of kidney fibrosis and human kidney biopsies from CKD patients. Bioinformatics analyses and experimental validation reveal that MMP-10 activated β-catenin in a Wnt-independent fashion. Knockdown of endogenous MMP-10 expression in vivo inhibited β-catenin activation and ameliorated kidney injury and fibrotic lesions, whereas over-expression of exogenous MMP-10 aggravated β-catenin activation and kidney fibrosis after injury. We found that MMP-10 cleaved and activated heparin-binding EGF-like growth factor (HB-EGF) via ectodomain shedding, leading to EGF receptor (EGFR) tyrosine phosphorylation and β-catenin transactivation via a cascade of events involving extracellular signal-regulated kinases and glycogen synthase kinase-3β. Consistently, treatment with erlotinib, a small-molecule EGFR inhibitor, effectively mitigated MMP-10-mediated kidney injury and fibrotic lesions in a dose-dependent fashion. Furthermore, β-catenin activation reciprocally upregulated the expression of MMP-10, thereby perpetuating kidney damage by forming a vicious cycle. Collectively, these results underscore that MMP-10 promotes kidney fibrosis through EGFR-mediated transactivating β-catenin in a Wnt-independent fashion. Our findings suggest that targeting MMP-10 could be a novel strategy for treatment of fibrotic CKD.